A facile one step route to synthesize WO3 nanoplatelets for CO oxidation and photodegradation of RhB: microstructural, optical and electrical studies. Issue 73 (21st July 2016) - Dirany, N.; Arab, M.; Madigou, V.; Leroux, Ch.; Gavarri, J. R.
Abstract : Two-dimensional nanoplatelets of WO3 were synthesized at room temperature. The large exposed (020) facets of the nanoplatelets show a high catalytic activities, for CO conversion and for photodegradation of organic pollutant. Abstract : Two-dimensional nanoplatelets of tungsten trioxide (NP-WO3 ) were synthesized at room temperature, using a wet chemical method, without any surfactants or templates; aqueous mineralization was obtained by simply adjusting the pH. The resulting nanostructures were characterized using X-ray diffraction combined with Rietveld refinements, Raman and UV-Vis spectroscopies. Their morphologies and sizes were analyzed by scanning and electron microscopies. The electrical, optical, catalytic and photocatalytic properties of the NP-WO3 nanoplatelets were then determined and compared to the ones of pseudospherical (PS-WO3 ) standard samples. Nanoplatelets as well as pseudospherical particles crystallized in the single orthorhombic WO3 phase. The Rietveld refinement calculations and HRTEM analyses revealed a strong distortion of the WO6 octahedra, according to the W–O splitting. The electrical conductivity of WO3 compact pellets showed that both samples were semi-conducting with a weak difference in activation energies. Using a homemade photocatalytic device, the NP-WO3 particles used as photocatalyst in an aqueous medium, exhibited a significant efficiency to decompose rhodamine B over their large exposed surface (010), compared to PS-WO3 particles. These NP-WO3 particles were also used as the catalytic material for oxidation in an air–CO gas flow. They exhibited catalytic activity higher than the one in the PS form.